Analisis Wujud Pelanggaran Prinsip Kesantunan dalam Film Pendek Tuku Sapi Satu Ton - Pramudyawatie, Yustina; Rini, Setia; Sari, Tri Novita (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2024)
This research examines the politeness principle in the short film Tuku Sapi Satu Ton by Herman Hadi Basuki. The aim is to describe the violation of politeness principles in the short film Tuku Sapi Satu Ton by Herman Hadi Basuki. This study uses a qualitative descriptive approach to language. The data collection method used in this research is the note-taking technique method. The listening technique in this study was used at the stage of watching the film and then proceeding with classification, while the note-taking technique was carried out when listening to the film followed by noting several utterances that contained violations of politeness principles in language. Data analysis was carried out using the equivalent method with a basic technique, namely the Sorting Elements (PUP) technique. The presentation of the data analysis used in this study is in an informal form by explaining the results of data analysis using sentences. The results of the study show that there are 7 utterances that violate the principle of politeness which include violations of the maxim of wisdom 2 data; generosity maxim 1 data; maxim of agreement 1 data; sympathy maxim 1 data; maximum reception of 1 data; maxim of humility 1 data. Based on the research results, the most dominant maxim of wisdom is found.